New sesquiterpenoid glycoside and phenylpropanoid glycosides from the tuber of Ophiopogon japonicus. Issue 6 (2nd June 2016) - Liu, Shi-Qiao; Kang, Li-Ping; Zhang, Jie; Liu, Yi-Xun; Zhao, Yang; Liu, Bin; Ma, Bai-Ping
Abstract: A new sesquiterpenoid glycoside, cryptomeridiol 11- O -β-d -xylopyranosyl-(1→6)-β-d - glucopyranoside (1 ), two new phenylpropanoid glycosides, 3, 4-dihydroxy-allylbenzene 3- O -β-d -glucopyranosyl-4- O -β-d -apiofuranosyl-(1→6)-β-d -glucopyranoside (2 ), and 3, 4, 5-trihydroxy-allylbenzene 3- O -β-d -glucopyranosyl-4- O -β-d -glucopyranoside (3 ), along with four known phenylpropanoid glycosides (4–7 ), were isolated from the tuber of Ophiopogon japonicus . Compounds4–7 were obtained from the genus Ophiopogon for the first time. Their structures were elucidated by spectroscopic methods, including 1D and 2D NMR and HR-ESI-MS.